2018
DOI: 10.1186/s12862-018-1135-z
|View full text |Cite
|
Sign up to set email alerts
|

The curious case of peroxiredoxin-5: what its absence in aves can tell us and how it can be used

Abstract: BackgroundPeroxiredoxins are ubiquitous thiol-dependent peroxidases that represent a major antioxidant defense in both prokaryotic cells and eukaryotic organisms. Among the six vertebrate peroxiredoxin isoforms, peroxiredoxin-5 (PRDX5) appears to be a particular peroxiredoxin, displaying a different catalytic mechanism, as well as a wider substrate specificity and subcellular distribution. In addition, several evolutionary peculiarities, such as loss of subcellular targeting in certain species, have been repor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
5
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 70 publications
1
5
0
1
Order By: Relevance
“…The loss of lymphotoxins in birds is not a rare event. Birds have the unique ability to compensate for losses in numerous immune genes/loci, including the Ig kappa L chain, peroxiredoxin, and other TNFSF members (15,(85)(86)(87). Thus, in agreement with previously published studies (32,54), we found that bird genomes do not contain TNFSF1, TNFSF3, or TNFRSF3.…”
Section: Discussionsupporting
confidence: 91%
“…The loss of lymphotoxins in birds is not a rare event. Birds have the unique ability to compensate for losses in numerous immune genes/loci, including the Ig kappa L chain, peroxiredoxin, and other TNFSF members (15,(85)(86)(87). Thus, in agreement with previously published studies (32,54), we found that bird genomes do not contain TNFSF1, TNFSF3, or TNFRSF3.…”
Section: Discussionsupporting
confidence: 91%
“…However, we cannot eliminate the possibility that ROSinduced DNA damage in mitochondrial DNA causes cell death in PRDX1-depleted cells. Among the 6 PRDX family genes reported in vertebrates, PRDX5, which contains the mitochondrial targeting sequence, is absent in the aves genome [32,33]. Aves PRDX1 localizes to the cytosol but may have an unknown role in the maintenance of mitochondrial ROS for proper cell growth.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, two alternative translation initiation sites lead to two forms of PRDX5: a long form (L‐PRDX5), which is addressed to mitochondria with the mitochondrial targeting sequence (MTS), and a short form (S‐PRDX5), which is located in the cytosol, nucleus and peroxisomes [11] . MTS in L‐PRDX5 is cleaved after mitochondrial import, producing a mature mitochondrial PRDX5 identical to S‐PRDX5 [12] . Therefore, in our previous investigation and this study, S‐PRDX5 was selected as the target protein for further research.…”
Section: Introductionmentioning
confidence: 99%